2017
DOI: 10.6018/analesps.33.3.276541
|View full text |Cite
|
Sign up to set email alerts
|

La frecuencia de las actividades sexuales como variable mediadora de la satisfacción sexual en mujeres jóvenes. (Frequency of sexual activities as a mediator of sexual satisfaction among young women.)

Abstract: Título: Satisfacción sexual en mujeres jóvenes: Frecuencia de las actividades sexuales como mediadora. Resumen: El objetivo del estudio fue analizar la relación entre varios predictores social-cognitivos del comportamiento sexual (creencias, conocimientos, actitudes y valores), las conductas sexuales, la frecuencia de actividades sexuales y diferentes dimensiones de la satisfacción sexual (individual/de pareja y actual/deseada). Para ello se utilizó un paradigma mixto de investigación. Para recabar los datos s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…A higher frequency of sexual activity has been shown to be beneficial for mental health since frequent sexual activity is associated with greater enjoyment of life [ 6 ], quality of life [ 7 ], well-being [ 8 ], and cognitive function [ 9 ] in older adults. Moreover, the benefits of regular sexual activity also extend to populations of younger adults; a recent study by Carcedo et al [ 10 ] observed higher levels of sexual satisfaction to be associated with lower levels of depression among Spanish young adults, which in turn has been observed to be mediated by the frequency of sexual activity [ 11 ]. Despite this knowledge, trends in the frequency of sexual inactivity among adults aged 18 to 44 years have importantly increased over recent decades in countries such as the United States [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher frequency of sexual activity has been shown to be beneficial for mental health since frequent sexual activity is associated with greater enjoyment of life [ 6 ], quality of life [ 7 ], well-being [ 8 ], and cognitive function [ 9 ] in older adults. Moreover, the benefits of regular sexual activity also extend to populations of younger adults; a recent study by Carcedo et al [ 10 ] observed higher levels of sexual satisfaction to be associated with lower levels of depression among Spanish young adults, which in turn has been observed to be mediated by the frequency of sexual activity [ 11 ]. Despite this knowledge, trends in the frequency of sexual inactivity among adults aged 18 to 44 years have importantly increased over recent decades in countries such as the United States [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the relationship between sexual behavior and its outcomes, considerable evidence supports the role for sexual satisfaction (e.g., Sánchez et al, 2012;Ogallar Blanco et al, 2017;Hawkins et al, 2022). Sexual satisfaction is not only linked to the frequency and diversity of sexual activities or the consistency of achieving orgasm but also to behaviors associated with intimacy, mood, and communication within intimate or sexual relationships (Fisher et al, 2015;Frederick et al, 2017;Schmiedeberg et al, 2017, Schoenfeld et al, 2017.…”
mentioning
confidence: 99%